A component of the mir-17-92 polycistronic oncomir promotes oncogene-dependent apoptosis - Olive, Virginie; Sabio, Erich; Bennett, Margaux J; De Jong, Caitlin S; Biton, Anne; McGann, James C; Greaney, Samantha K; Sodir, Nicole M; Zhou, Alicia Y; Balakrishnan, Asha; Foth, Mona; Luftig, Micah A; et al. (eLife, 2013)
mir-17-92, a potent polycistronic oncomir, encodes six mature miRNAs with complex modes of interactions. In the Eμ-myc Burkitt’s lymphoma model, mir-17-92 exhibits potent oncogenic activity by repressing c-Myc-induced apoptosis, primarily through its miR-19 components. Surprisingly, mir-17-92 also encodes the miR-92 component that negatively regulates its oncogenic cooperation with c-Myc. This miR-92 effect is, at least in part, mediated by its direct repression of Fbw7, which promotes the proteosomal degradation of c-Myc. Thus, overexpressing miR-92 leads to aberrant c-Myc increase, imposing a strong coupling between excessive proliferation and p53-dependent apoptosis. Interestingly, miR-92 antagonizes the oncogenic miR-19 miRNAs; and such functional interaction coordinates proliferation and apoptosis during c-Myc-induced oncogenesis. This miR-19:miR-92 antagonism is disrupted in B-lymphoma cells that favor a greater increase of miR-19 over miR-92. Altogether, we suggest a new paradigm whereby the unique gene structure of a polycistronic oncomir confers an intricate balance between oncogene and tumor suppressor crosstalk.
Keywords: microRNA; c-Myc; Eμ-myc lymphoma; apoptosis; p53